Implementasi Model Project Based Learning terhadap Hasil Belajar pada Mata Pelajaran Produk Kreatif dan Kewirausahaan (PKK) pada Kelas XI Jurusan Teknik Pemesinan di SMK Negeri 2 Dumai - nst, Hafizd Syahiran; Abadi, Zainal; Waskito, Waskito; Purwantono, Purwantono (ALSYS, 2024)
Vocational education is designed to develop skills, abilities, understanding, teamwork attitudes and an appreciation that includes the knowledge and information needed by a worker to enter and make progress in a useful and productive job. Factors that support the creation of quality graduates are found in the subjects of Creative Products and Entrepreneurship. This study aims to analyze the Implementation of the Project Based Learning Model on Learning Outcomes in Creative Products and Entrepreneurship (PKK) Subjects in Class XI of the Machining Engineering Department at SMK Negeri 2 Dumai. This research is a class action research (PTK) or often also called classroom action research. This Jhon Elliot model classroom action research consists of pre-cycle, first cycle and second cycle to achieve the desired results. This study uses an instrument in the form of an assessment rubric that is used to see student learning outcomes in creative product and entrepreneurship subjects with the application of project-based learning models referring to the results of projects made by students. Based on the results of research and discussion, class action research on the subject of Creative Products and Entrepreneurship in class XI Machining Engineering SMK N 2 Dumai can be concluded as follows. 1) Efforts to improve learning outcomes using project-based learning models in class XI TP in the subject of Creative Products and Entrepreneurship have been successfully implemented and are able to improve student learning outcomes at SMK Negeri 2 Dumai. 2) With the project-based learning model, teachers have other choices in determining learning models so that it can be a solution in improving student learning outcomes.